The tumor-suppressor and cell adhesion molecule Fat controls planar polarity via physical interactions with Atrophin, a transcriptional co-repressor. - Fanto, M.; Clayton, L.; Meredith, J.; Hardiman, K.; Charroux, B.; Kerridge, S.; McNeill, H. (Development, 2003)
Fat is an atypical cadherin that controls both cell growth and planar polarity. Atrophin is a nuclear co-repressor that is also essential for planar polarity; however, it is not known what genes Atrophin controls in planar polarity, or how Atrophin activity is regulated during the establishment of planar polarity. We show that Atrophin binds to the cytoplasmic domain of Fat and that Atrophin mutants show strong genetic interactions with fat. We find that both Atrophin and fat clones in the eye have non-autonomous disruptions in planar polarity that are restricted to the polar border of clones and that there is rescue of planar polarity defects on the equatorial border of these clones. Both fat and Atrophin are required to control four-jointed expression. In addition our mosaic analysis demonstrates an enhanced requirement for Atrophin in the R3 photoreceptor. These data lead us to a model in which fat and Atrophin act twice in the determination of planar polarity in the eye: first in setting up positional information through the production of a planar polarity diffusible signal, and later in R3 fate determination.